The Effectiveness of Flashcards as a Learning Medium on Japanese Hiragana Writing Skills of Students at SMAN 4 Padang - Putri, Rika Roza; Purnawan, Ari (Riviera Publishing, 2026)
This study aims to: (1) Determine the students ability to write hiragana using flashcard-based learning in Grade XI at SMAN 4 Padang, (2) Determine the students ability to write hiragana without using flashcard-based learning medi in Grade XI at SMAN4 Padang, (3) Determine the effectiveness of using flashcard learning media on the Japanese hiragana writing ability of Grade XI students at SMAN 4 Padang. The scope of this study is limited to the effectiveness of using flashcard learning media on the ability to write seion, dakuon, and handakuon types of hiragana among students of classes XI F3 and XI F5 at SMAN 4 Padang. The method used in this study is a quantitative quasi-experimental approach using the Nonequivalent Control Group Design, in which the researcher compares the results of two groups consisting of an experimental class and a control class, but the groups are not randomly selected and are determined using purposive sampling. Data collection was carried out through observation and the administration of pretests and posttest in each class. The instruments used in the study include a hiragana writing test and a flashcard media quationnaire. The data were analyzed using the Normality test, Wilcoxon test, and Mann- Whitney test.The result of the study show that, (1) The learning outcomes of hiragana using flashcard learning media in the experimental class (XI F5) obtained an average pretest score of 69.8 and a average posttest score of 82.2, (2) The learning outcomes of hiragana without using flashcard learning media in the control class (XI F3) obtained an average pretest score of 71.4 and a average posttest score of 80, this indicates that there is a difference in scores betweem the experimental and control classes, (3) After statistical hypothesis testing was conducted using SPSS version 26 with Mann-Whitney test, the result of Asymp. Sig (2-tailed) was 0.971 > 0.05, which means there is no statistically significant difference between the posttest scores of the two groups being compared, namely the experimental and control classes. Therefore, the use of flashcard media does not have a significant effect on the hiragana writing ability of the evelent-grade students at SMAN 4 Padang, with the null hypothesis (H0) accepted and the alternative hypothesis (H1) rejected.